An Affective-Appraisal Approach for Parental Shared Decision Making in Children and Young People's Mental Health Settings: A Qualitative Study - Liverpool, Shaun; Hayes, Daniel; Edbrooke-Childs, Julian (Frontiers in Psychiatry, 2021)
Background: The majority of existing shared decision making (SDM) models are yet to explicitly account for emotion as an influencing factor to the SDM process. This study aimed to explore the role of parents’ and carers’ emotional experiences as a concept that has implications for SDM in children and young people’s mental health (CYPMH) settings. Methods: A social constructivist grounded theory approach, analysing data from focus groups (n=4) and semi-structured interviews (n=33) with parents and healthcare professionals, was undertaken. Participants were identified and selected at CYPMH sites and through social media platforms or in-person advertising as part of a larger feasibility trial. Interviews and focus groups were audio-recorded and transcribed verbatim. Thematic analysis moved from open to focused coding. Results: The majority of the sample consisted of mothers of adolescent girls. Healthcare professionals had an average of 7.54 (SD=6.24) years of work experience in CYPMH outpatient capacities. Findings suggested that parents are ‘expected to, but not always able to’ engage in SDM. Themes and subthemes described an affective-appraisal SDM process capturing: 1) views and experiences of SDM, 2) parents’ emotional states, 3) the influence of emotions on SDM, and 4) key support systems accessed. The emerging affective-appraisal framework highlighted that negative emotional states hindered parents’ active involvement in SDM, and positive emotions encouraged involvement in SDM. Conclusion: The current findings describe an SDM model specific to CYPMH. This new understanding contributes to addressing a possible theory to practice gap opening new challenges and opportunities for academic enquiry.